Process, Equipment, and Materials Control in Integrated Circuit Manufacturing V 1999
DOI: 10.1117/12.361314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEB temperature profile on CD for DUV resists

Abstract: The effect of varying time and temperature profile at the PEB step on a 250 nm isolated line is studied for an Acetal and an ESCAP type Deep UV (DUV) resist. Experimental studies on the Acetal resist resulted in very non-linear Critical Dimension (CD) sensitivities with CD variation largest for low Post Expose Bake (PEB) temperature and short PEB time. A global CD model was created by fitting experimental data to a first order kinetics equation. An effective activation energy of 50 Kcal/mole was obtained for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The present problem can also be solved in a steady state domain for the following reasons. Although transient effects could affect the CD uniformity to an extent [11,12], the photo-chemistry and hence the CD accuracy is more sensitive only after the wafer reaches the amplification threshold of T SET [10]. Hence the 120 s baking process is done in two phases.…”
Section: Inverse Heat Conduction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present problem can also be solved in a steady state domain for the following reasons. Although transient effects could affect the CD uniformity to an extent [11,12], the photo-chemistry and hence the CD accuracy is more sensitive only after the wafer reaches the amplification threshold of T SET [10]. Hence the 120 s baking process is done in two phases.…”
Section: Inverse Heat Conduction Methodsmentioning
confidence: 99%
“…Because of the negligible wafer thickness ($1 mm) when compared to the heater thickness (30 mm, for 'thin' bake plates [10], which is used in this study), simulation studies [23] have shown that the thermal resistance of the air in the proximity gap (see Fig. 1(a)) allows the lateral conduction in the wafer, improving the temperature uniformity of the wafer.…”
Section: Methods Of Heat Flux Re-distributionmentioning
confidence: 99%
See 1 more Smart Citation